The Effect of Managerial Ownership, Institutional Ownership, Independent Commissioners, Audit Committee on Company Value (IDX 30 2018-2020) - Doloksaribu, Eveline Angelica; Hutapea, Joan Yuliana (STKIP Yapis Dompu, 2022)
The purpose of this research is to find out the effect of managerial ownership, institutional ownership, independent commissioners, audit committees on firm value (IDX 30 2018-2020). This research was conducted using a quantitative approach, especially linear multiple regression analysis. This study uses Agenc Theory and Signaling Theory to show that institutional ownership, independent commissioners, and audit committees have an effect on firm value. The results of this study indicate that managerial ownership has an influence on firm value. Institutional ownership variable has no substantial effect on firm value. The independent commissioner variable has no significant effect on business value. The audit committee variable has no significant effect on firm value.